Analysis of Epidemiology and Risk Factors of Atopic Dermatitis in Korean Children and Adolescents from the 2010 Korean National Health and Nutrition Examination Survey. (22nd August 2017) - Lee, Kyung Suk; Oh, In-Hwan; Choi, Sun Hee; Rha, Yeong-Ho
Abstract : Background. Atopic dermatitis (AD) is a common chronic inflammatory skin disease, but only few studies involved samples of children and adolescents that are representative of the entire Korean population. This study aimed to estimate the prevalence and risk factors of AD among children and adolescents in Korea by using nationally representative data. Methods. We used data from the fifth Korean National Health and Nutrition Examination Survey in 2010 and retrospectively evaluated 2, 116 children and adolescents. Logistic regression analysis was performed to determine the relationship between AD and other variables, including IgE levels. Results. The prevalence rate of AD in children and adolescents was 15.0%. In the multivariate analysis of ages from 1 to 18 years, age (adjusted odds ratio [aOR], 0.96; p < 0.01 ) was related to AD. From age of 12 to 18 years, smoking (aOR, 8.99; p < 0.01 ) and elevated total IgE serum level (aOR, 5.31; p < 0.01 ) were related to AD. Conclusion. Age, smoking, and elevated total IgE level were related to AD in the children and adolescents. Thus, an antismoking policy and public education are necessary for reducing the prevalence of allergic diseases. In addition, measurement of total IgE level and age may be helpful in the diagnosis of AD.